Combined Application of Malic Acid and Lycopene Maintains Content of Phenols, Antioxidant Activity, and Membrane Integrity to Delay the Pericarp Browning of Litchi Fruit During Storage - Huang, Hua; Wang, Ling; Bi, Fangcheng; Xiang, Xu (Frontiers in Nutrition, 2022)
Litchi fruit contains abundant polyphenols and is susceptible to browning after harvest. Herein the combined treatments of malic acid (MA) and lycopene (LYC) to delay the development of browning in litchi fruit stored at room temperature (25 oC) and low temperature (4 oC) was investigated. The results showed that the pericarp browning could be alleviated, and the increase of MDA content and relative leakage rate were retarded by the combined MA and LYC during storage. As compared to control, the content of main antioxidants of anthocyanins, flavonoids as well as the total phenols maintained higher levels; and the decrease of antioxidant activity of DPPH radical scavenging capacity and reducing power were slowed down in treated fruit. The enzyme activity of PPO and POD related to oxidation of polyphenols were depressed by the combined treatments. Furthermore, correlation analysis revealed that the content of phenols in pericarp negatively affected the changes in browning index, and positively related to antioxidant activity such as the DPPH radical scavenging capacity. Taken together, the combined treatment of MA and LYC exhibited potential effects in delaying the rapid browning of litchi fruit by maintaining the content of polyphenols, antioxidant activity and membrane integrity.